Targeting Copper Dyshomeostasis as a Pathophysiological Basis of Childhood Obesity: Latest Facts - Marina Jaksic; Milica Martinovic; Mirjana Nedovic Vukovic (Mazandaran University of Medical Sciences, 2024)
Context: Childhood pre-obesity and obesity rates have been rapidly growing worldwide over the past decades. Copper homeostasis is gaining increasing attention in the physiopathology of obesity. Strong evidence indicates that a disturbance of copper homeostasis plays an important role in the development of obesity and its related comorbidities. Under physiological conditions, copper plays a significant role in regulatory, immunologic, and antioxidant functions resulting in protection against inflammation and oxidative stress, and consequently against the known comorbidities of obesity. Nevertheless, despite the growing body of research, information about copper status in obesity, particularly in childhood obesity, is scarce.  Evidence Acquisition: This brief narrative review examines the latest data published in the last five years using various databases, such as PubMed, Scopus, Unpaywall (COBISS), and EBSCO to emphasize the major current findings in research related to this topic.  Results: The most recent studies have yielded strong evidence in support of altered copper status in childhood obesity; nevertheless. Conclusions: Further studies are needed to clarify the role of copper in the physiopathology of childhood obesity.